2019
DOI: 10.1039/c9ce00847k
|View full text |Cite|
|
Sign up to set email alerts
|

Polymorphism of levofloxacin: structure, properties and phase transformation

Abstract: The landscape of solid-state crystal forms of levofloxacin is further expanded with one solved anhydrous α form and three newly discovered solvates including n-propanol solvate, ethylene glycol solvate and acetic acid solvate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 16 publications
2
20
0
Order By: Relevance
“…Deviations between experiment and simulation at longer mixing times are due to multispin effects associated with the contributions from multiple fluorine atoms in the crystal lattice. The short 19 F interfluorine distance in this polymorph is consistent with frequently observed crystal structures of levoflaxicin (Figure d). The 2D 1 H– 19 F and ( 1 H) 13 C– 19 F HETCOR spectra provide further information about the intermolecular interactions present in this polymorph, also consistent with known crystal structures of levofloxacin (Figure S4).…”
Section: Resultssupporting
confidence: 89%
“…Deviations between experiment and simulation at longer mixing times are due to multispin effects associated with the contributions from multiple fluorine atoms in the crystal lattice. The short 19 F interfluorine distance in this polymorph is consistent with frequently observed crystal structures of levoflaxicin (Figure d). The 2D 1 H– 19 F and ( 1 H) 13 C– 19 F HETCOR spectra provide further information about the intermolecular interactions present in this polymorph, also consistent with known crystal structures of levofloxacin (Figure S4).…”
Section: Resultssupporting
confidence: 89%
“…Naturally, many antibiotics have hydrate forms, which are commonly more stable than solvates, with different physicochemical properties, such as density, the molecular weight of the crystal, solubility, stability, hygroscopicity, etc. [18,26,56]. More importantly, the solvent or water portion should adjust the dose required, which is often unfixed or unpredictable.…”
Section: Hydrate and Solvatementioning
confidence: 99%
“…12 Mid-infrared spectroscopy can display information related to inter/intramolecular interactions that are the result of different polymorphic structures. 13 However, unlike in the fields of pharmaceuticals and energetic materials, there are almost no reports of the quantification of polymorphs in agrochemicals in the literature, patents and standards. Through a literature search, it can be found that the use of univariate and multivariate data analysis coupled with solid-state analytical methods is a common approach to solve the challenges of the classification and quantification of different polymorphs in pharmaceutical substances and energetic materials.…”
Section: Introductionmentioning
confidence: 99%